2022
DOI: 10.1007/s00432-022-04167-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mindfulness yoga on anxiety and depression in early breast cancer patients received adjuvant chemotherapy: a randomized clinical trial

Abstract: Purpose The objective of this study is to explore the effects of a mindfulness yoga treatment on emotional disorders, fatigue, pain, and health-related quality of life in early-stage breast cancer patients. Methods The eligible 136 participants were randomly assigned 1:1 to the experimental group (mindfulness yoga + conventional care) and the control group (conventional care). The hospital anxiety and depression scale was used to assess anxiety and depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 37 publications
1
34
0
2
Order By: Relevance
“…Finally, this study included 18 studies. [13–30] See the Flowchart . Table 1 shows the characteristics of the study and the participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study included 18 studies. [13–30] See the Flowchart . Table 1 shows the characteristics of the study and the participants.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the study and participants Author Liu [13] 2022 Cramer [17] 2015 Jong [22] 2018 Netherlands Yoga:47 Cai [26] 2022 China Yoga:36 CG:37 51.17 Li [28] Sensitivity analysis was conducted to identify the potential sources of heterogeneity. Even after excluding all studies, the findings remained unchanged, demonstrating that the findings were stable.…”
Section: Tablementioning
confidence: 99%
“…Healthcare providers should include MBE as a routine supplementary treatment option alongside medication for patients suffering from mental health disorders. Notably, four included studies reported adverse events related to excessive or incorrect yoga practice (Danhauer et al, 2009; Jong et al, 2018; Kiecolt‐Glaser et al, 2014; Liu et al, 2022). Compared to Liuzijue or other types of qigong, Pilates and yoga are typically more challenging to perform and may need the assistance of a trained instructor to ensure proper execution (Shi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety are the main psychological problems faced by breast cancer patients. Long-term psychological distress will reduce the survival rate of breast cancer patients, while firstline medications for emotional disorders will also increase the mortality of breast cancer patients (Liu et al, 2022). Therefore, mindfulness therapy as a non-pharmacological treatment is essential.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies on the impact of MBSR on breast cancer patients have not considered the effects according to the stage of breast cancer. Therefore, in a recent study, Liu et al (2022) conducted MBSR intervention on patients with early breast cancer. Early breast cancer patients are considered curable, but there is no denying that they will still have mental health problems and other complications.…”
Section: Studies Focused On the Effects Of Mbsr On Depression And Anx...mentioning
confidence: 99%